KOMODIFIKASI JILBAB DALAM SEJARAH PERADABAN MANUSIA - Marinda, Leny (LP2M IAIN Jember, 2019)
Hijab or khimar which is interpreted as a head covering for Muslim women is an interesting theme to be discussed. It is not something new when Islam was born. The discussion has crossed various levels in the history of human life from time to time. Hijab and khimar explained clearly in Al Ahzab: 59 and An Nur: 31. The context of the descent of the verses is related to the social, cultural, economic and security of the Muslim community. The development of interpretations of religious, social and cultural texts bring diverse views about Hijab. Now, the hijab ,with all its dynamics, has an important position in Muslim life that deserves attention. Hijab atau khimar yang diartikan sebagai penutup kepala bagi wanita muslimah menjadi tema yang menarik untuk dibahas. Bukan hal baru ketika Islam lahir. Pembahasan telah melintasi berbagai tingkatan dalam sejarah kehidupan manusia dari masa ke masa. Hijab dan khimar dijelaskan secara gamblang dalam Al Ahzab: 59 dan An Nur: 31. Konteks turunnya ayat tersebut terkait dengan sosial, budaya, ekonomi dan keamanan umat Islam. Perkembangan tafsir teks agama, sosial dan budaya membawa pandangan yang beragam tentang hijab. Kini, hijab dengan segala dinamikanya memiliki posisi penting dalam kehidupan muslim yang patut mendapat perhatian.